SOSIALISASI HUKUM, PELATIHAN & PENINGKATAN PENDIDIKAN FORMAL MAUPUN NON FORMAL PADA PESERTA DIDIK - Nirwan Junus; Mutia Cherawaty Thalib; Karlin Z. Mamu (Univeristas Negeri Gorontalo, 2022)
The problems of teenangers are increasingly complex and concerning, especially in the current era of globalization. The rise of liquor in teenagers and the problem of gambling in the general public are certainly triggers for conflict, in addition, problems in the field of education, namely the lack of educators at SDN 11 Batudaa Pantai, difficulties for children in learning, such as the Koran, reading and arithmetic must can be solved. Therefore, the approach taken is through education and law counseling. The targets of this program are 1) to carry out socialization/law counseling in order to provide understanding and increase public legal awareness, especially in teenagers, 2) to provide assistance in order to improve student learning patterns in terms of reading and arithmetic, 3) to help educators in SDN 11 Batudaa Pantai in minimizing the problems faced, especially in terms of reading and arithmetic and 4) re-activating the TPA which has long been absent, and 5) Empowering the younger generation of Lamu Village to be more creative in developing the village. The method used in this activity is to provide socialization/legal counseling to the community, as well as providing assistance to students in reading and arithmetic.